2015
DOI: 10.6026/97320630011203
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal drug resistance pattern of Candida. spp isolated from vaginitis in Ilam-Iran during 2013-2014

Abstract: Vaginal Candidiasis is the most common and important opportunistic fungal infection in women. By increasing use of antifungal drugs in recent years, it has caused drug resistance. This study aims to evaluate antifungal drugs susceptibility of Candida. spp isolated of women with vaginitis from Ilam-Iran during 2013-2014. samples were collected and cultured from 385 women with vaginitis, then Candida.spp was diagnosed by standard method. Antifungal drug susceptibility test for nystatin 100 unit/disk, fluconazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
6
11
0
1
Order By: Relevance
“…The findings revealed that the prevalence of Candida vaginitis was 160 (51.6%). These results are similar to Mohamadi et al (17), Hedayati et al (15), and Rasti et al's studies (18). Furthermore, the present study indicated the high rate of VVC in 30-to 40-year-olds, which is in agreement with the study of Mohamadi et al (17), while it is in contrast with Rezaei-Matekolaei et al (19).…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that the prevalence of Candida vaginitis was 160 (51.6%). These results are similar to Mohamadi et al (17), Hedayati et al (15), and Rasti et al's studies (18). Furthermore, the present study indicated the high rate of VVC in 30-to 40-year-olds, which is in agreement with the study of Mohamadi et al (17), while it is in contrast with Rezaei-Matekolaei et al (19).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, a different frequency of VVC (39.76%) was reported when compared to our previous studies in Ahvaz in 2016 (28.3%) and 2010 (49%) (15,21). The frequency of VVC in other cities in Iran was reported as 62.1%, 43.3%, 40%, 26%, and 4.8% from Ilam, Babol, Arak, Hamadan, and Zanjan, respectively (12,13,16,31,32).…”
Section: Discussionmentioning
confidence: 98%
“…Pregnancy, contraception drugs with high estrogen, antibiotic consumptions, uncontrolled diabetes, immunosuppressive drugs, unsafe or excessive sexual intercourse, chronic anemia and season allergy are some predisposing factors of VC. The most common signs of VC are vaginal itching, dysuria and malodorous-white vaginal secretions [ 4 ]. Treatment of VC varies substantially and the most common drugs used are azole agents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%